Leading Nursing Into the Future: Development of a Strategic Nursing Platform on a System Level. Issue 3 (July 2015) - Young, Joyce; Landstrom, Gay; Rosenberger, Susan; Guidroz, Ashley M.; Albu, Alice
Abstract : Leading and orchestrating the mission-essential work of 47 diverse hospitals toward a common vision with a supporting strategy is a challenge for any health care system. Trinity Health embraced this challenge while reorganizing the pivotal role of nursing in designing the future of health care delivery. This article outlines the roadmap utilized to create a common nursing platform to drive strategy aligned to future viability, strength, and growth across a system. Abstract : Supplemental Digital Content is Available in the Text.